Three-Phase Induction Motor Drives with Back-to-Back Converter Using Field-Oriented Control and Voltage-Oriented Control - รุจิดามพ์, นาวี (Srinakharinwirot University Engineering Journal, 2018)
This paper presents the three-phase induction motor drives with back-to-back converter which is divided into two sides. Three-phase full-bridge converter using voltage-oriented control is connected with grid-side, and three-phase three-leg voltage source converter control by means of rotor field-oriented control in motor-side. Three-phase induction motor drive system in the paper is simulated with the help of MATLAB/Simulink. The simulation results revealed that three-phase induction motor had satisfactory performance and fast response. Meanwhile, grid-side converter was capable of bi-directional power flow, kept dc-link voltage constant at 700 Volt, and had power factor of grid and total harmonic distortion of grid current, which was 0.922 and 2.33 percentage.